Body composition after endoscopic lung volume reduction with endobronchial valves: a prospective study - Brock, Judith; Rott, Christina; Limen, Eldridge Frederick; Kontogianni, Konstantina; Gompelmann, Daniela; Herth, Felix (Respiration, 2024)
Introduction: Patients with chronic obstructive pulmonary disease (COPD) and emphysema experience malnutrition and pulmonary cachexia. Endoscopic lung volume reduction (ELVR) with endobronchial valves has not only improved lung function, exercise capacity, and quality of life but also influenced body weight. Only a few data are available on body composition changes after ELVR. Methods: This single-center prospective study of patients with advanced COPD investigates body composition before and after endoscopic valve treatment using multifrequency bioelectrical impedance analysis (BIA). The following parameters were evaluated in addition to clinical data and routine tests: body weight, body mass index (BMI), basal metabolic rate, total body water, body fat, cell percentage, phase angle, intracellular water (ICW), extracellular water (ECW), extracellular mass (ECM), body cell mass (BCM), lean body mass (ECM + BCM), and fat-free mass index. Results: A total of 23 patients (mean emphysema index 37.2 ± 7.5%, BMI 23.4 ± 4.3 kg/m2) experienced improvements in lung function and exercise capacity with ELVR. Complete lobar atelectasis was achieved in 39.1% of participants. A non-statistically significant increase in body weight and BMI was observed after ELVR (p = 0.111 and p = 0.102). BIA measurement revealed a worsening of phase angle, cell percentage and ECM/BCM and thus of body composition, but without statistical significance. This is mainly due to a statistically significant increase in ECM, ECW, and ICW (all p < 0.001). Conclusion: ELVR demonstrated no beneficial changes in body composition, although patients tend to gain weight. A larger cohort is warranted to confirm these findings.
Online veröffentlicht: 13. Juni 2024
Gesehen am 18.11.2024